Teachers’ knowledge and implementation of inquiry-based-learning in elementary science education: a phenomenological study in indonesia - Nurhairani, Nurhairani; Suyanta, Suyanta; Haryanto, Haryanto (Jurnal Ilmiah Pendidikan Dasar, 2026)
Science education in Indonesian elementary schools currently faces significant challenges in fostering students' critical and scientific thinking skills and positioning them as active learning subjects. A key contributing factor is teachers' insufficient knowledge regarding the effective implementation of Inquiry-Based Learning (IBL), which consequently diminishes student engagement. This phenomenological study, utilising a qualitative approach, investigates elementary school teachers' understanding of IBL and analyses its practical application in science classrooms. Data were gathered through open-ended questionnaires, interviews, and literature review, involving 74 in-service teachers distributed across Indonesia's Western, Central, and Eastern regions. The findings reveal significant conceptual gaps among teachers. Particularly, teachers demonstrated a limited and often inaccurate understanding of IBL's core principles, indicating prevalent misconceptions. This knowledge deficit critically hinders the effective implementation of IBL in science instruction. Furthermore, the study identified pronounced disparities in IBL knowledge between teachers in the Western, Central, and Eastern regions, highlighting distinct regional inequities. The study emphatically concludes that the systemic integration of IBL into elementary science education is imperative. Achieving this necessitates targeted professional development programs specifically designed to address the identified knowledge gaps and regional disparities among teachers.